0019 Identifying The Targets Of Estradiol In HUVECs Exposed To Intermittent Hypoxia: The Possible Involvement Of ATM-cIAP Pathway. (12th April 2019) - Lin, Ying Ni; Lan, Xiao Fei; Liu, Zhuo Ran; Yan, Ya Ru; Zhou, Joan Ping; Li, Qing Yun
Abstract: Introduction: Chronic intermittent hypoxia (CIH) contributes to the increased risk of cardiovascular diseases in obstructive sleep apnea (OSA) through inducing oxidative stress and increasing endothelial cell apoptosis. We previously reported anti-oxidant and anti-apoptotic effects of estradiol (E2) on IH-exposed human umbilical vein endothelial cells (HUVECs). In this study, we employed a proteomic analysis to elucidate the molecular mechanisms of protective effects of estradiol under IH exposure. Methods: HUVECs were divided into the four groups: control, IH, IH+E2 (cells were exposed to IH with 17β-estradiol treatment), and IH+si-Txnip (thioredoxin-interacting protein-knock-down cells were exposed to IH) group. Then, isobaric tags for relative and absolute quantification (iTRAQ) was performed to compare protein profiles among the groups. Results: A total of 185 proteins changed significantly in IH+E2 compared to IH group. Bioinformatics analysis indicated that the effect of estradiol may be linked to the regulation of cellular stress response. We further identified that serine-protein kinase ataxia telangiectasia mutated (ATM), and its downstream target cellular inhibitor of apoptosis protein (cIAP) were up-regulated by E2. Since thioredoxin/thioredoxin-interacting protein (Trx1/Txnip) pathway is involved in the effect of E2 on IH-exposed HUVECs, we also compared the protein expression profiles between IH+si-Txnip and IH group. We identified that 15 proteins, including ATM, changed significantly in both IH+E2 and IH+si-Txnip group compared to IH group. Conclusion: These results indicated that estradiol may protect against oxidative stress and endothelial apoptosis through promoting ATM and c-IAPs expressions under IH exposure. This effect of estradiol may involve its regulation of Trx1/Txnip pathway. The findings may provide valuable clues for exploring the target(s) for prevention and treatment of the cardiovascular complication in OSA patients. Support (If Any): This work was funded by the National Natural Science Foundation of China (81700084, 81070068, 81770084, 81570082, 81700085) and Shanghai Key Discipline for Respiratory Disease (2017ZZ02014), Key Research Program of Shanghai Science and Technology Commission (18140903600).